2012
DOI: 10.1162/jocn_a_00070
|View full text |Cite
|
Sign up to set email alerts
|

Study–Test Congruency Affects Encoding-related Brain Activity for Some but Not All Stimulus Materials

Abstract: Memory improves when encoding and retrieval processes overlap. Here, we investigated how the neural bases of long-term memory encoding vary as a function of the degree to which functional processes engaged at study are engaged again at test. In an incidental learning paradigm, electrical brain activity was recorded from the scalps of healthy adults while they made size judgments on intermixed series of pictures and words. After a 1-hr delay, memory for the items was tested with a recognition task incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…First, an important difference between these studies is that the face stimuli used in Righi et al are fundamentally different from the realistic pictures used in the other studies. Materials effects may account for differences between these studies, given that ERP correlates of memory can differ according to the materials used both at encoding and retrieval (Bauch and Otten, 2012;Yick and Wilding, 2008). Second, the lack of EEM effects in Galli et al and the absence of emotional effects on source memory performance in Koenig and Mecklinger may have been caused by the utilisation of a short study-test interval in both of these studies.…”
Section: Introductionmentioning
confidence: 96%
“…First, an important difference between these studies is that the face stimuli used in Righi et al are fundamentally different from the realistic pictures used in the other studies. Materials effects may account for differences between these studies, given that ERP correlates of memory can differ according to the materials used both at encoding and retrieval (Bauch and Otten, 2012;Yick and Wilding, 2008). Second, the lack of EEM effects in Galli et al and the absence of emotional effects on source memory performance in Koenig and Mecklinger may have been caused by the utilisation of a short study-test interval in both of these studies.…”
Section: Introductionmentioning
confidence: 96%
“…rhyme vs semantic processing, (Morris, Bransford, & Franks, 1977). Similar effects have also been found with manipulating the modality in which items are presented at encoding and retrieval, for instance using pictures and words (Bauch & Otten, 2012;Mcdermott & Roediger, 1994), or presenting words visually and aurally (Mulligan & Osborn, 2009). In cognitive psychology these match/mismatch effects can be subsumed under the terms Encoding Specificity Principle (Tulving & Thomson, 1973), or Transfer Appropriate Processing (Morris et al, 1977).…”
Section: Introductionmentioning
confidence: 55%
“…This core prediction of the TAP account has received support from imaging studies (Bauch and Otten, 2012; Fellner et al, 2013; Staudigl and Hanslmayr, 2013; Staudigl et al, 2015; Vogelsang et al, 2016, 2018; Long and Kahana, 2017). Here, we replicate and extend the results from these previous studies by showing that the cortical reinstatement of the encoding brain patterns is only associated with beneficial effects for remembering if the replayed patterns are task relevant.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, previous studies have shown that encoding-related brain activity (i.e., predictive of subsequent memory) is shaped both by the type of processing occurring at encoding and by the overlap between encoding and retrieval processes (Bauch and Otten, 2012; Fellner et al, 2013; Staudigl and Hanslmayr, 2013; Vogelsang et al, 2016; 2018; Long and Kahana, 2017). The typical procedure in these previous studies has been to investigate encoding-related brain activity when explicitly instructing participants to attend to particular attributes during the encoding and retrieval.…”
Section: Introductionmentioning
confidence: 99%